Gender identity as a barrier to accessing adequate and inclusive healthcare for Syrian refugees in Lebanon's Northern regions - Diab, Jasmin Lilian; Samneh, Bechara; Masoud, Dima; Cravero, Kathleen (Frontiers in Human Dynamics, 2024)
The structure and modes of operation of Lebanon’s healthcare system cast a blind eye upon refugees’ specific challenges and needs. It not only remains highly privatized, but additionally involves a number of exclusionary practices across both private and public sectors. This reality, coupled with political agendas, partisan politics, clientelism, and an overall lack of transparency at the level of public administration, gives private health providers substantial amounts of subjective influence – and more importantly, the authority to be exclusionary. This article explores how gender identity has impacted access to healthcare services for the Syrian refugee community since 2019 – with a specific focus on women and members of the LGBTIQ+ community. The study focuses on the regions of Tripoli and Akkar – regions found to be tainted by socio-cultural sensitivities hindering women and LGBTIQ+ individuals from being honest and expressive about the gender-specific care they need, and thus, hindering adequate service provision. Specifically, the research aims to implore an intersectional lens to exploring health, gender and displacement in application. Specifically, it aims to respond to the following questions: (1) To what extent have gender identity, gender expression and gender norms impacted Syrian refugees’ ability to access gender-sensitive health services in Tripoli and Akkar?; (2) To what extent have the aforementioned gender considerations, when intersecting with refugee status, served as an added layer/barrier to accessing health services in Tripoli and Akkar?; (3) To what extent do socio-cultural norms in Tripoli and Akkar impact Syrian refugee women and LGBTIQ+ refugees’ ability to be honest and transparent about their specific health needs? (4) To what extent does the nature of the Lebanese health system, coupled with the limited knowledge among healthcare providers around gender-sensitive care, serve as a catalyst towards exclusionary health access for refugees first, and for sexual and gender minorities (SGM) second?